Psychiatric disorders in 22q11.2 deletion syndrome are prevalent but undertreated. Issue 6 (April 2014) - Tang, S. X.; Yi, J. J.; Calkins, M. E.; Whinna, D. A.; Kohler, C. G.; Souders, M. C.; McDonald-McGinn, D. M.; Zackai, E. H.; Emanuel, B. S.; Gur, R. C.; Gur, R. E.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Chromosome 22q11.2 deletion syndrome (22q11DS) is a common genetic disorder with high rates of psychosis and other psychopathologies, but few studies discuss treatment. Our aim was to characterize the prevalence and treatment of major psychiatric illnesses in a well-characterized sample of individuals with 22q11DS. Method This was a cross-sectional study of 112 individuals aged 8 to 45 years with a confirmed diagnosis of 22q11DS. Each participant was administered a modified Schedule for Affective Disorders and Schizophrenia for School-Age Children (K-SADS) and the Structured Interview for Prodromal Syndromes (SIPS). Phenotypes assessed were threshold and subthreshold psychosis, depression, mania, generalized and separation anxiety, obsessions/compulsions, inattention/hyperactivity and substance use. Histories of mental health care and current psychotropic treatment were obtained. Results Psychopathology was common, with 79% of individuals meeting diagnostic criteria for a disorder at the time of assessment. Diagnoses of psychosis were made in 11% of cases, attenuated positive symptom syndrome (APS) in 21%, and 47% experienced significant subthreshold symptoms. Peak occurrence of psychosis risk was during adolescence (62% of those aged 12–17 years). Criteria for a mood disorder were met by 14%, for anxiety disorder 34% and for attention deficit hyperactivity disorder (ADHD) 31%. Mental health care had been received by 63% of individuals in their lifetime, but only 40% continued therapy and 39% used psychotropics. Antipsychotics were used by 42% of participants with psychosis and none of the participants with APS. Half of those at risk for psychosis were receiving no mental health care. Conclusions Psychopathology is common in 22q11DS but is not adequately treated or clinically followed. Particular attention should be paid to subthreshold psychotic symptoms, especially in adolescents.